2009
DOI: 10.1128/jb.00668-09
|View full text |Cite
|
Sign up to set email alerts
|

tIS Cpe8 , an IS 1595 -Family Lincomycin Resistance Element Located on a Conjugative Plasmid in Clostridium perfringens

Abstract: Clostridium perfringens is a normal gastrointestinal organism that is a reservoir for antibiotic resistance genes and can potentially act as a source from which mobile elements and their associated resistance determinants can be transferred to other bacterial pathogens. Lincomycin resistance in C. perfringens is common and is usually encoded by erm genes that confer macrolide-lincosamide-streptogramin B resistance. In this study we identified strains that are lincomycin resistant but erythromycin sensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…IMEs generally encode their own relaxase and frequently few other proteins involved in conjugation such as the coupling protein. However, five IMEs that do not encode any protein involved in their transfer were recently identified (Achard and Leclercq, 2007; Lyras et al ., 2009; Daccord et al ., 2010). These elements, also described as mobile genomic islands (Daccord et al ., 2010), or transferable insertion sequences (Lyras et al ., 2009) carry their own oriT being processed by the relaxase of the mobilizing element.…”
Section: Discussionmentioning
confidence: 99%
“…IMEs generally encode their own relaxase and frequently few other proteins involved in conjugation such as the coupling protein. However, five IMEs that do not encode any protein involved in their transfer were recently identified (Achard and Leclercq, 2007; Lyras et al ., 2009; Daccord et al ., 2010). These elements, also described as mobile genomic islands (Daccord et al ., 2010), or transferable insertion sequences (Lyras et al ., 2009) carry their own oriT being processed by the relaxase of the mobilizing element.…”
Section: Discussionmentioning
confidence: 99%
“…As for transfer of all other tested IMEs, the mobilization of a MGI to a recipient is independent of any cotransfer of the helper ICE, the transconjugants harboring the MGI alone (the most frequent), the ICE alone, or the two elements. Even more unusual IMEs from firmicutes, MTnSag1 (Achard & Leclercq, 2007) and its relative tISCpe8 (Lyras et al, 2009), were found to be mobilizable by Tn916. These elements that can be considered as insertion sequences harboring a passenger gene (Siguier et al, 2009) only encode a lincosamide resistance and a DDE transposase, responsible for the formation of a circular extrachromosomal form of the IME and for its insertion (Achard & Leclercq, 2007).…”
Section: Mobilization Diversitymentioning
confidence: 99%
“…Another putative IME encoding a serine recombinase, ICE6180-RD.1, seems to be site-specifically integrated in the 3′ end of rumA that encodes a 23S rRNA methyltransferase (Beres & Musser, 2007). Finally, MTnSag1 from S. agalactiae and the related element tISCpe8 from C. perfringens encode a DDE transposase belonging to IS1595 family and have a low specificity of integration (Achard & Leclercq, 2007;Lyras et al, 2009).…”
Section: Integration Diversitymentioning
confidence: 99%
“…CpCP plasmids belong to the pCW3 family and are widely spread among isolates of C. perfringens, carrying genes encoding AbR (tetracycline [tetAB(P)], chloramphenicol [catP-Tn4451], lincomycin [lnuP-tISCpe8]) and/or enterotoxins, ε-toxin, or iota-toxin production that determine different toxinotypes (56,(229)(230)(231). All pCW3-like plasmids have a conjugative transfer locus of 11 open reading frames (orfs) (tcp [transfer C. perfringens]) that includes an integrase and a T4CP protein but lacks relaxase (73,231).…”
Section: Clostridiummentioning
confidence: 99%